Meningkatkan Komitmen dan Kinerja Dosen: Apa Peran Manajemen Perguruan Tinggi? - Rachma Nadhila Sudiyono; Francisca Sestri Goestjahjanti; Masduki Asbari; Eva Agistiawati; Miyv Fayzhall; Ahmad Yani; Winanti Winanti; Teguh Yuwono; Nurasiah Nurasiah; Yayah Yulia; Eman Singgih; Gusli Chidir (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aimed to measure the effect of perceived organizational support on the affective commitment and performance of private higher education lecturers in Tangerang which are mediated by lecturer engagement. Data collection was done by simple random sampling via electronic to the private higher education lecturer population in Tangerang. The returned and valid questionnaire results were 231 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that perceived organizational support have a positive and significant effect on the affective commitment and lecturer performance, both directly and indirectly through mediating lecturer engagement. This new research proposed a model for building the affective commitment and performance among the private higher education lecturers in Tangerang through enhancing perceived organizational support with lecturer engagement as a mediator. This research could pave the way to improve lecturer readiness in facing the era of education 4.0.